IMF Staff papers : Volume 28 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1981)
The paper discusses the application of economic analysis and statistics to several questions of tax administration and legislation bearing on it. The principle of equalizing marginal administrative costs and marginal tax revenue is suggestive, but persuasive arguments can be made for spending more or less than it indicates. The marginal principle, nevertheless, is valuable as a guide for allocating a fixed appropriation that is too small to cover all remunerative activities. Human capital theory corroborates the productivity of staff training but implies that different financing arrangements may be appropriate for general and specialized training. Economic studies can help in establishing criteria for identifying cases for detailed examination or audit and in making administrative or alternative assessments where accounts are inadequate. A lump-sum, first-year depreciation allowance equal to the discounted value of normal allowances would have merit as a simple method of adjusting for inflation. Tax administrators and economists could benefit from acquaintance with the attitudes and methods of each other's discipline.